Komunikasi Perubahan Sosial Dalam Perilaku Orang yang Sedang Jatuh Cinta Terhadap Lingkungan Sekitar - Qiaufy Tahania; Nina Yuliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research was conducted using interview data regarding changes in a person's attitude or behavior when they fall in love which have an impact on the surrounding environment. This research was created in order to understand the impact of changes in a person's behavior. This research aims to explore and understand the role of communication in stimulating social change in the behavior of individuals who are experiencing a phase of falling in love with the surrounding environment. This research uses a qualitative approach, case study method, and descriptive research type. The results of the research show that this change in behavior tends to provide positive changes, affecting their awareness and the intensity of feelings is the main factor in this change in behavior.